Chloride capping of CdTiO3 for higher crystallinity and enhanced photocatalytic activity. Issue 3 (17th December 2015) - Shah, Zameer Hussain; Ge, Yuzhen; Lin, Xijie; Xiu, Jinghai; Zhang, Shufen; Lu, Rongwen
Abstract : The crystallinity of cadmium titanate (CdTiO3 ) was greatly improved when synthesized under mild reaction conditions, in the presence of chloride. Abstract : The crystallinity of cadmium titanate (CdTiO3 ) was greatly improved when synthesized under mild reaction conditions, in the presence of chloride. The highly crystalline CdTiO3 showed much enhanced photodegradation of methyl orange (MO) under simulated sunlight. CdTiO3 was characterized using X-ray diffraction (XRD), transmission electron microscopy (TEM), X-ray photoelectron spectroscopy (XPS), N2 adsorption/desorption, photoluminescence (PL), and UV/vis spectrometry. The enhanced photodegradation was attributed to the better charge separation owing to its higher crystallinity.